WAYS TO USE MODERN METHODS IN THE MANAGEMENT OF HIGHER EDUCATIONAL INSTITUTIONS: CARA-CARA UNTUK MENGGUNAKAN METODE MODERN DALAM PENGELOLAAN INSTITUSI PENDIDIKAN TINGGI - Alimardonovich, Alimardonov Asrorjon (Academia Open, 2025)
General Background: Uzbekistan’s higher education sector has undergone extensive reforms in recent years, aligning institutional practices with global standards. Specific Background: Despite policy shifts toward digitalization, strategic planning, and international accreditation, the integration of modern management practices across institutions remains inconsistent. Knowledge Gap: Although global models such as KPI systems and distributed leadership are promoted, there is a lack of structured, context-sensitive studies examining their applicability within Uzbekistan’s higher education system. Aims: This study investigates the implementation of strategic management, digital platforms, shared governance, and benchmarking in Uzbek universities to develop practical, localized management models. Results: Findings show progress in digital transformation and internationalization (e.g., widespread LMS adoption and accreditation gains), yet highlight deficits in leadership capacity, institutional strategy formulation, and integration of global best practices. Novelty: The research introduces a comprehensive framework that harmonizes strategic KPIs, digital tools, and participatory leadership while emphasizing the human dimension of management reform. Implications: The proposed model offers actionable policy recommendations that bridge global innovations with national realities, supporting sustainable modernization in higher education governance. Highlights: Strategic Planning is Crucial Universities must move beyond “plans on paper” and adopt clear KPIs and feedback systems to drive real outcomes. Digital Management is the Future Integrated platforms (like LMS, ERP) are essential to synchronize education, finance, and HR systems for efficiency. Localized Internationalization Global best practices should be adapted—not copied—into national contexts to ensure sustainable modernization. Keywords: Higher Education, Strategic Management, Digitalization, KPI Systems, Leadership